Social capital and neighbourhood cooperation: Implications for development of the urban poor in LDCs. (October 2019) - Bashar, Toriqul; Bramley, Glen
'Neighbourhood cooperation' can be viewed as a key element for livelihood improvement, particularly within areas of urban poverty in Least Developed Countries (LDCs). Such cooperation might be useful for mobilising resources and sharing risks of investing in infrastructures/services and maintaining common goods. This article explores the structural relationships between individual level cooperation and overall social capital, in relation to household and neighbourhood characteristics. These relationships are complex as various factors are interlinked, which influence cooperation at both individual and group levels. Literature on social capital has relied mainly on Western countries; from this starting point, this article analyses the relationships among aspects of social capital. Analytical models are based on Durlauf's approach of measuring 'social capital' and Manski's perspective on social interaction, which are tested on 1800 households' data across three locations in Bangladesh. The estimates reveal that individual level cooperation can be influenced directly by households' socio economic circumstances and indirectly through neighbourhood mediation, while questioning some theoretical generalisations about neighbourhood cooperation. The findings contribute to the literature on neighbourhood effects by revealing that: (a) the relationship between one's socio economic status and one's social capital is less clear than expected; and (b) extreme poverty and proximity of living in a neighbourhood can promote norms of trust and cooperation.